2023
DOI: 10.3389/fnut.2023.1198796
|View full text |Cite
|
Sign up to set email alerts
|

Associations of lifestyle with mental health and well-being in Chinese adults: a nationwide study

Abstract: BackgroundA healthy lifestyle is beneficial to individuals’ health. However, little is known about the associations of lifestyle factors with mental health and well-being. This study examined the associations of lifestyle factors with mental health (i.e., depression, anxiety, loneliness, perceived pressure, and self-rated health status) and well-being in Chinese adults.MethodsA nationally representative survey was conducted in China from 20 June 2022 to 31 August 2022. Data from the survey were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…This finding was similar to a Swiss national health survey [ 33 ], which found that lonely participants were prone to unhealthy lifestyle behaviors, such as smoking, being less physically active, and less fruit and vegetable consumption when compared with participants who never felt lonely. A national wide survey among Chinese adults also showed a negative associations between lifestyle scores and loneliness [ 34 ]. The reason why lonely individuals are easier to have a poor healthy lifestyle may be related with their poor self-motivation, low spiritual growth, insufficient social support and increased social isolation [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was similar to a Swiss national health survey [ 33 ], which found that lonely participants were prone to unhealthy lifestyle behaviors, such as smoking, being less physically active, and less fruit and vegetable consumption when compared with participants who never felt lonely. A national wide survey among Chinese adults also showed a negative associations between lifestyle scores and loneliness [ 34 ]. The reason why lonely individuals are easier to have a poor healthy lifestyle may be related with their poor self-motivation, low spiritual growth, insufficient social support and increased social isolation [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that more severe depression symptoms were associated with worse eating behaviors, which was consistent with prior research [ 70 , 71 ]. Individuals with depression symptoms are more likely to increase unhealthy food consumption [ 72 ] and have unhealthy eating habits [ 73 ]. Furthermore, depression affects eating motivations and drives food choices toward less healthy foods [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the key risk factors for anxiety and depression disorders, diet-related factors are faced by people on a daily basis [12]. Many studies have demonstrated that adherence to healthy eating behavior reduces anxiety and depression symptoms [5,[12][13][14][15][16] In contrast, unhealthy eating behavior are related to an increased risk of anxiety and depression [17][18][19]. It is worth noting that people consume meals made up of a variety of food groups, and complicated combinations of foods can have synergistic effects [20,21].…”
Section: Introductionmentioning
confidence: 99%